An eye on light-sheet microscopy - Kromm, Dimitri; Thumberger, Thomas; Wittbrodt, Joachim (The zebrafish ; part A: Cellular biology, 2016)
This chapter introduces the principles and advantages of selective plane illumination microscopy (SPIM) and compares it to commonly used epifluorescence or confocal setups. Due to the low phototoxicity, speed of imaging, high penetration depth, and spatiotemporal resolution, SPIM is predestined for in vivo imaging but can as well be used for in toto analysis of large fixed samples. Key points of light-sheet microscopy are highlighted and discussed priming the investigator to choose the best suitable system from the large collection of possible SPIM setups. Mounting of samples is shown and the demands for data acquisition, processing, handling, and visualization are discussed.